HUBUNGAN KONSUMSI SAYURAN DAN BUAH, ASUPAN ZAT GIZI MAKRO DAN AKTIVITAS FISIK DENGAN STATUS GIZI REMAJA - Lillah Rizqi Fauziah; Veni Indrawati (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2023)
Adolescence is a transition phase from childhood to adulthood. The adolescent age group of 10-19 is very vulnerable to nutritional problems, because at that age adolescents experience hormonal changes which may affect their physical changes. Nutritional problems in adolescents appear due to nutritional behavior and misunderstanding of consumption and balanced nutritional needs. This study aims to determine the relationship between vegetables and fruits consumption, macronutrients intake, and physical activity with nutritional status in adolescents in Wiyung district. This research is a quantitative research with a cross sectional approach. Respondents of this study are 96 teenagers. Data was collected using the SQ-FFQ form, 2x24 hour food recall form, Physical Activity Questionnaire for Adolescents (PAQ-A) and direct measurements of body weight and height. Data analysis using Spearman's rank test. The results of the study based on female gender showed that there was a significant relationship between vegetable consumption (p=0.000), fruit consumption (p=0.001), energy intake (p=0.004), fat intake (p=0.001), carbohydrate intake (p=0.000) , and physical activity (p=0.000) with the nutritional status of adolescents. Meanwhile, protein intake (p=0.185) had no correlation with the nutritional status of adolescents. The results of the study based on male gender showed that there was a significant relationship between energy intake (p=0.004), protein intake (p=0.000), fat intake (p=0.046), carbohydrate intake (p=0.004), and physical activity (p = 0.002) with the nutritional status of adolescents. Meanwhile, vegetable consumption (p=0.341) and fruit consumption (p=0.947) had no correlation with adolescent nutritional status.Usia remaja merupakan kondisi peralihan masa anak- anak menuju dewasa. Kelompok usia remaja 10-19 tahun termasuk kelompok yang sangat rentan terhadap permasalahan gizi, dikarenakan pada usia tersebut remaja mengalami perubahan hormonal dan berpengaruh pada perubahan fisiknya. Permasalahan gizi pada remaja timbul akibat perilaku gizi dan pemahaman yang salah mengenai konsumsi dan kebutuhan gizi yang seimbang. Penelitian ini bertujuan untuk mengetahui hubungan konsumsi sayur dan buah, asupan zat gizi makro dan aktivitas fisik dengan status gizi pada remaja di kecamatan wiyung surabaya. Jenis penelitian ini yaitu penelitian kuantitatif dengan pendekatan Cross Sectional. Responden penelitian ini berjumlah 96 remaja. Data dikumpulkan menggunakan formulir SQ-FFQ, formulir food recall 2x24 jam, Physical Activity Questionnaire for Adolescents (PAQ-A) serta pengukuran berat badan dan tinggi badan secara langsung. Analisis data dengan menggunakan uji rank spearman. Hasil penelitian berdasarkan jenis kelamin perempuan menunjukkan terdapat hubungan yang signifikan konsumsi sayur (p=0,000), konsumsi buah (p=0,001), asupan energi (p=0,004), asupan lemak (p=0,001), asupan karbohidrat (p=0,000), dan aktivitas fisik (p=0,000) dengan status gizi remaja. Sedangkan asupan protein (p=0,185) tidak memiliki korelasi dengan status gizi remaja. Hasil penelitian berdasarkan jenis kelamin laki-laki menunjukkan terdapat hubungan yang signifikan asupan energi (p=0,004), asupan protein (p=0,000), asupan lemak (p=0,046), asupan karbohidrat (p=0,004), dan aktivitas fisik (p=0,002) dengan status gizi remaja. Sedangkan konsumsi sayur (p=0,341) dan konsumsi buah (p=0,947) tidak memiliki korelasi dengan status gizi remaja.